The autoimmune diseases - Rose, Noel R.; Mackay, Ian R. (Elsevier / Academic Press, 2006)
Provides the understanding of the immune mechanisms underlying autoimmunity and autoimmune disease. This book combines common themes underlying inductive and effector mechanisms and therapies that relate generally to the autoimmune disorders. It discusses the biological basis of disease at genetic, molecular, cellular, and epidemiologic levels.